Decades of Educational Excellence: A Case Study of A Successful Family-Owned Higher Educational Institution - Macasinag, Maria Luz (JPAIR Institutional Research, 2019)
This study critically examined a successful family-owned higher educational institution to identify the attributes and practices that may have led to its success. This research was confined to a private, non-sectarian, family-owned higher institution of learning that has been operating for more than fifty years, had only one founder, and had at least two transitions in terms of generation. Findings revealed nine themes – the presence of a positive (1) corporate culture and values, (2) shared vision, (3) corporate social responsibility, effective (4) corporate governance, a strong (5) human resource development program, a transformative (6) style of leadership, (7) strong family culture, (8) succession plan and effective (9) business strategies, attributes and practices contributory to the success of a family-owned higher education institution. Significantly, the dominant theme was anchored on corporate culture and values, which reflect the family orientation not only of the leaders in the institution but also the general culture of the Filipino people. It is concluded that these various themes form part of the holistic model that can appropriately analyze family firm performance in the field of education in terms of sustainability through several generations. Ultimately, sociological factors dominated this study’s results, reflecting how culture impacts different processes and structures in a family-owned Higher Education Institution.